Mechanical properties of basalt macro fibre reinforced geopolymer concrete - Huang, Zhijie; So, Cek; Chen, Wensu; Htet, Paing; Hao, Hong (2024)
Growing public environmental awareness leads to an increased focus on utilizing green and sustainable materials in infrastructure construction. Geopolymer concrete (GPC) and basalt macro fibres (BMFs) are promising construction materials due to their eco-friendly merits and excellent mechanical properties. In this study, a new type of BMFs reinforced GPC (BMF-GPC) was developed, and the compressive and flexural properties of BMF-GPC were investigated. The effects of BMF content and length on the mechanical properties of GPC were studied. It was found that with the addition of 2 % BMFs, the compressive and flexural toughness (energy absorption capacities) of GPC were greatly enhanced by up to 126 % and 965 %, respectively. Increasing the content and length of BMFs resulted in favourable outcomes for strain softening of GPC under compression and post-cracking behaviour of GPC under flexural loads, whilst having limited effects on the modulus of elasticity and flexural strength. Additionally, an analytical model was proposed to predict the compressive stress-strain behaviour of BMF-GPC, which could be used for the design of BMF-GPC structures.